Examining the military–media nexus in ISIS's provincial photography campaign. Issue 2 (4th May 2018) - El Damanhoury, Kareem; Winkler, Carol; Kaczkowski, Wojciech; Dicker, Aaron
Abstract: Islamic State in Iraq and Syria (ISIS) views military action and media operations as two equally important, reinforcing components of its campaign. With provinces disseminating 95% of ISIS's media output, provincial media play a central role in achieving appearance shifts in the contested balance of power. Yet, scholars have not fully examined the interactions between the media and military components of ISIS's campaign at the provincial level. To understand how enhanced coalition military operations impact the quantity and content of provincial media output, this study examines all 1643 photographs that Ninawa province disseminated before and during intense battles in the east Mosul operation. Unlike the common views in earlier studies, our study reveals that Ninawa's use of still imagery, in particular, tripled following the launch of the Mosul operation, and the depiction of the state-building campaign remained intact. ISIS also used about-to-die images as its image weaponry of choice during intensified military pressure. Here, we use the case of Ninawa province to explore how ISIS can create nuanced photographic campaigns to help offset losses on the contested media battlefield and facilitate future repackaging of content. Finally, we highlight the importance of operationalization for a better understanding of the military–media nexus in future studies.